2014
DOI: 10.3168/jds.2013-7807
|View full text |Cite
|
Sign up to set email alerts
|

Dietary modulation of the expression of genes involved in short-chain fatty acid absorption in the rumen epithelium is related to short-chain fatty acid concentration and pH in the rumen of goats

Abstract: We have tested the hypothesis that increased concentrate intake induces mRNA abundance alterations of genes involved in short-chain fatty acid (SCFA) absorption in the rumen epithelium of goats and these changes of mRNA abundance are probably related to ruminal SCFA concentration and ruminal pH. Goats (n=12) were randomly allocated to 2 groups and fed either a low-concentrate (LC) diet (10% concentrate; n=6) or a medium-concentrate (MC) diet (35% concentrate; n=6) in 2 equal portions daily. Goats were fed sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 28 publications
8
51
2
Order By: Relevance
“…In this study, the physiological pH and the physiological concentration of SCFAs promoted the expression of MCT1 in the ruminal epithelium cells, which were consistent with the available in vivo data. Yan, Zhang, and Shen () reported that the decline of rumen pH and the rise of SCFAs concentration in the physiological range of rumen promoted the expression of the gene of MCT1 and MCT4. Thus, the balance between the rates of production and resorption SCFAs in rumen fluid played an important role in maintaining health through maintaining the metabolic balance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the physiological pH and the physiological concentration of SCFAs promoted the expression of MCT1 in the ruminal epithelium cells, which were consistent with the available in vivo data. Yan, Zhang, and Shen () reported that the decline of rumen pH and the rise of SCFAs concentration in the physiological range of rumen promoted the expression of the gene of MCT1 and MCT4. Thus, the balance between the rates of production and resorption SCFAs in rumen fluid played an important role in maintaining health through maintaining the metabolic balance.…”
Section: Discussionmentioning
confidence: 99%
“…Glyceraldehyde-3-phosphate dehydrogenase (GADPH) was chosen as the housekeeping gene. The primers of 11 genes were designed in this study according to the available sequences in NCBI, and the primers of the remaining 11 genes were synthesized according to the description of Yan et al (2014) (Supplementary Table S2). The amplification efficiency of the primers was determined by means of a dilution series of epithelial cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…A study on mice revealed that diet enhanced immune tolerance also by affecting the interactions of pattern-recognition receptors (PRPs) and commensals in GI tract (Zelante et al, 2013). Our previous studies have shown that the increased intake of non-fiber carbohydrate (NFC), which can be rapidly fermented by GI microbes, causes the significant increases in the concentrations of butyrate, acetate and propionate in goat rumen (Yan et al, 2014; Lu et al, 2015). However, yet little is known about the diet-induced specification of ruminal microbiota and their effects on the immune tolerance of rumen epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous study has demonstrated that the classical “job sharing” in epithelia between NHE3 (transepithelial Na transport) and NHE1 (regulation of pH i ) probably also occurred in the rumen epithelium (Rabbani, Siegling‐Vlitakis, Noci, & Martens, ). Our previous work has shown that feeding high concentrate diets could upregulate the expression of NHE in rumen epithelium, which help to the maintenance of intracellular pH homeostasis (Yan, Zhang, & Shen, ; Yang et al., ).…”
Section: Introductionmentioning
confidence: 99%